FACTORS AFFECTING THE INTEGRITY OF FINANCIAL STATEMENTS : BEFORE AND DURING THE PANDEMIC - Asfeni Nurullah; Tertarto Wahyudi; Syarah Lutfa Aliya (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
The target of this research is to establish the effect from auditor switching, audit tenure, and financial distress on the integrity of economic statements before and through the pandemic. The subject of this research are the financial sectors registered on the Indonesia Stock Exchange between years of 2019 and 2020. This research method uses a quantitative method. The population that been used are companies in the financial sector between years of 2019 and 2020. The sample of the population that been used were taken using a purposive sampling technique, counted as 106 samples. Data were analyzed using the Statistical Program for Social Software (SPSS) version 24.0 using descriptive statistics and multiple linear regression. The financial statements integrity in this study is measured using conservatism. The results of the study partially show that auditor switching and audit tenure have no significant effect on the financial statements integrity before the pandemic and through the pandemic, while financial distress has no effect on the integrity of financial statements pre-pandemic financial statements but has a significant negative effect on the financial statements significant at the time of the pandemic. There was a significant difference between the financial statements significant before and through the COVID-19 pandemic.